2013
DOI: 10.17711/sm.0185-3325.2013.033
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la melatonina sobre la macro-arquitectura del sueño en pacientes con demencia tipo Alzheimer

Abstract: SUMMARYThe objective of the present study was to evaluate the 5 mg. melatonin effects on the sleep macro-architecture in eight patients with middle to moderate Alzheimer´s disease (DTA). Using the polysomnographic technique (PSG), we made a simple-blind, non-randomized, controlled with placebo study. The PSG was carried out according to the following order: night 1: placebo administration; night 2 and 3: continues melatonin administration. In the first night with melatonin treatment, the sleep latency to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Though the placebo group experienced no significant changes in overall sleep scores as measured by the Pittsburgh Sleep Quality Index (PSQI), the melatonin group experienced an improvement in overall sleep scores, as indicated by a significant decrease in PSQI scores [ 47 ]. These results agree with Cruz-Aguilar et al [ 95 , 96 ], who observed that melatonin (5-mg, fast-release) supplementation had a beneficial impact on sleep among individuals with mild-to-moderate AD ( n = 8) by reducing sleep latency. In contrast, an earlier clinical trial observed no significant differences in sleep measures using wrist actigraphy among individuals with AD supplemented with either 2.5 mg prolonged-release melatonin, 10 mg fast-release melatonin, or a placebo for eight weeks [ 97 ].…”
Section: Melatoninsupporting
confidence: 92%
See 1 more Smart Citation
“…Though the placebo group experienced no significant changes in overall sleep scores as measured by the Pittsburgh Sleep Quality Index (PSQI), the melatonin group experienced an improvement in overall sleep scores, as indicated by a significant decrease in PSQI scores [ 47 ]. These results agree with Cruz-Aguilar et al [ 95 , 96 ], who observed that melatonin (5-mg, fast-release) supplementation had a beneficial impact on sleep among individuals with mild-to-moderate AD ( n = 8) by reducing sleep latency. In contrast, an earlier clinical trial observed no significant differences in sleep measures using wrist actigraphy among individuals with AD supplemented with either 2.5 mg prolonged-release melatonin, 10 mg fast-release melatonin, or a placebo for eight weeks [ 97 ].…”
Section: Melatoninsupporting
confidence: 92%
“…While the exact mechanism of melatonin in AD remains unclear, melatonin may play a beneficial role in AD by improving circadian rhythms and reducing inflammation, oxidative stress, and the formation of Aβ plaque and NFT [ 88 , 90 , 98 ]. Both Wade et al [ 47 ] and Cruz-Aguilar et al [ 95 , 96 ] observed a significant improvement in sleep among individuals with mild-to-moderate AD following melatonin supplementation. As a result, the beneficial role of melatonin in AD may be due to its ability to restore disruptions in circadian rhythms.…”
Section: Melatoninmentioning
confidence: 99%
“…The effects of add-on 2 mg PRM to standard therapy (acetylcholinesterase inhibitors with or without memantine) on sleep scores of AD patients were measured by the Pittsburgh Sleep Quality Index (PSQI) and a sleep diary in the study of Wade et al [68]. The timing and duration of the treatment are given in Table 1 Non-randomized controlled trials 5 mg IRM was found effective in improving sleep parameters in middle-tomoderate AD patients in the study conducted by Cruz-Aguilar et al [69]. The timing and duration of the treatment are given in Table 1.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%